Purchase Recommendations for Globalizing Online Collections at Community College Libraries. Issue 1 (2nd April 2016) - Harris, Annie Kadala
ABSTRACT: Focused on community colleges in North Carolina participating in the Scholars of Global Distinction initiative, the goal of this article is to assist librarians in their efforts to thoughtfully increase global and area studies online resources available at their libraries. Through this article, the author hopes to increase global library resources around North Carolina without duplicating research efforts across the state. The author reviews online paid resources that are global in scope or that provide the information commonly sought by community college students in globalized courses. For each database, the author considers the following criteria: global content, depth of coverage, accuracy, currency, authority, source information, usability, special features, and suitability for community college users. After being reviewed individually, the databases are compared within groups on the above criteria. Finally, the reviewer takes into account current pricing of the databases prior to making final recommendations.